The impact of exchange rate misalignment on portfolio inflows in Malaysia - Mohd Sidek, Noor Zahirah; Yusoff, Mohammed (Inderscience Publishers, 2010)
The primary reason why exchange rate misalignment is of interest to economists lie with the notional premise that risks emanating from overvaluation may undermine the competitiveness of Malaysia as a destination for portfolio investment inflows. On the other hand, undervaluation should make her a more attractive host. This study presents an attempt to examine the impact of exchange rate misalignment on portfolio inflows in Malaysia. Results show that events of misalignment have a negative impact on portfolio inflows. Specifically, overvaluation has significant deterrent effect on portfolio inflows but the opposite could not be implied in the case of undervaluation. Therefore, exchange rate policies should be geared to keep the exchange rate in line with the economic fundamentals so as to avoid prolonged overvaluation.